Impact of Fire on Mechanical Properties of Lightweight Bricks Containing Calcium Carbide Residue - Cut Rahmawati; Meliyana Meliyana; Ibnu Thufail; Muhtadin Muhtadin; Muhammad Faisal (Jurnal Inotera, 2020)
Calcium carbide residue is an unutilized by-product. It contains high calcium and can be used to produce cementitious. The variation of Calcium carbide residue used is 0%, 5%, and 15%. This study focused on the reduction of the cement used and lightweight bricks resistance toward the fire condition. Moreover, the tests were carried out by examining the compressive strength before and after lightweight bricks burned, X-ray fluorescence (XRF), Scanning Electron Microscope (SEM), and Fourier-Transform Infrared Spectroscopy (FTIR). The result showed a decrease of compressive strength on 10% and 15% carbide variation. At the combustion temperature of 250 °C, micro-cracking occurred at 0% and 5% carbide specimens, while not only cracking but also spalling and crazing were at the specimens with 10% carbide. The 5% variation of calcium carbide residue can increase the compressive strength and endurance at 250 °C. At the higher temperature, the compressive strength was decreased, and the material was damaged. IR-spectroscopy test results showed that 5% carbide composition achieved the highest compressive strength because the amount of H2O2 used reacts with CaO.